(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aims to identify the concept of trading securities in Iraq and to propose a new mechanism for the taxation of trading profits and the extent of its impact on tax revenues, as it was observed that there are professional investors in the trading market and some of them achieve huge annual profits. and this profit should be like other taxable profits. The General Commission of Taxes and in cooperation with the Iraq Stock Exchange should identifying those profits, subjecting them to income tax, and adding them to the tax base. The researcher relied on the use of the descriptive and analytical approach based on the data and information of the Iraq Stock Exchange and the General Commission for Taxes and related laws and instructions. The research concluded, through analyzing the indicators of the Iraq stock exchange and applying the tax model on a sample of investors, that the tax on dividends and bonds has a role in increasing tax revenues. The tax on stock and bond profits has a role in increasing tax revenues, and it must activate the work of a tax law by imposing a tax on the profits of securities trading and give it great importance in the event that it is activated, and It is very important to work on selecting qualified and competent staff who are able to succeed and implement this tax